2017
DOI: 10.1111/jnc.14077
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neurotoxicity of the organophosphorus insecticide chlorpyrifos: from clinical findings to preclinical models and potential mechanisms

Abstract: Organophosphorus (OP) insecticides are pest-control agents heavily used worldwide. Unfortunately, they are also well known for the toxic effects that they can trigger in humans. Clinical manifestations of an acute exposure of humans to OP insecticides include a well-defined cholinergic crisis that develops as a result of the irreversible inhibition of acetylcholinesterase (AChE), the enzyme that hydrolyzes the neurotransmitter acetylcholine (ACh). Prolonged exposures to levels of OP insecticides that are insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(83 citation statements)
references
References 134 publications
0
83
0
Order By: Relevance
“…Another pyrethroid pesticide, cypermethrin, also stimulated GSK-3β-dependent increase in Aβ and phosphor (p)-tau in rats [59]. In the same light, the organophosphate pesticide chlorpyrifos, which inhibit acetylcholinesterase [60], upregulates Aβ and tau in SN56 basal forebrain cholinergic neurons [61] and in mice [62], as well as p-tau via activation of GSK-3β [61]. DDT also increases Aβ levels in H4 glioma cells with a APP Swe transgene via elevation of APP and BACE1, while decreasing the levels of Aβ-clearing ATP-binding cassette transporter A1 (ABCA1) and inhibiting the activity of Aβ-degrading insulin-degrading enzyme (IDE) [63].…”
Section: Pesticides and The Induction Of Alzheimer's Disease Markersmentioning
confidence: 95%
“…Another pyrethroid pesticide, cypermethrin, also stimulated GSK-3β-dependent increase in Aβ and phosphor (p)-tau in rats [59]. In the same light, the organophosphate pesticide chlorpyrifos, which inhibit acetylcholinesterase [60], upregulates Aβ and tau in SN56 basal forebrain cholinergic neurons [61] and in mice [62], as well as p-tau via activation of GSK-3β [61]. DDT also increases Aβ levels in H4 glioma cells with a APP Swe transgene via elevation of APP and BACE1, while decreasing the levels of Aβ-clearing ATP-binding cassette transporter A1 (ABCA1) and inhibiting the activity of Aβ-degrading insulin-degrading enzyme (IDE) [63].…”
Section: Pesticides and The Induction Of Alzheimer's Disease Markersmentioning
confidence: 95%
“…While these levels are many orders of magnitude lower than the doses administered to postnatal rats in this study, it is critical to remember that the human data re ect estimated average daily exposures and do not take into account exposures during periods of active pesticide exposure in the home, school or nearby agricultural elds. A more relevant comparison is CPF levels in human cord blood at birth, which range from 3.7 pg/g (Rauh et al 2011) to > 6.17 pg/g (Burke et al 2017). The peak level of CPF in the blood of PND 5 rats dosed with CPF at 1 mg/kg in DMSO (s.c.) was approximately 9 ng/ml (Marty et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As to humans, it has been reported that children exposed to a high concentration of CPF in utero show an inverse dose–response relationship between CPF and cortical thickness, and a dose‐related association with slower brain growth (Rauh et al, ; Rauh et al, ). Epidemiological studies have reported statistically significant correlations between prenatal subacute exposures to organophosphate insecticides, including chlorpyrifos, and neurological deficits that range from cognitive impairments to tremors in childhood (Burke et al, ). Pharmacokinetic studies in rodents have shown that chlorpyrifos‐thionate is rapidly metabolized in the mother prior to crossing the placenta, and so the fetus is primarily exposed to the metabolite chlorpyrifos‐oxon (CPF‐oxon) (Abdel‐Rahman et al, ).…”
Section: Chemical Agentsmentioning
confidence: 99%